La educomunicación para la alfabetización ecológica y la construcción participativa de una cultura ambiental en niños - Erwin Hernando Jácome Castilla; Naydú Judith Jácome Castilla; Eduardo Luis Jácome Castilla (Mundo Fesc)
In recent decades, the world has experienced profound changes, which have generated various environmental problems on the planet. Regarding this reality, the United Nations Environment Program (UNDP) presents a diagnosis that highlights the current crisis. Regarding this, it is worth highlighting that it is partly caused by "the extraction of natural resources," which has been growing at an exponential rate, since this extractive activity has tripled since 1970. Additionally, the 45% increase in fossil fuel consumption worsens the global situation [1]. As an alternative solution to this glocal scenario, an analysis of the communication model used by primary school natural science teachers was conducted to build a solid environmental culture in children. Regarding the methodology, the research was developed with a qualitative approach, within the framework of a participatory methodology supported by the application of semi-structured interviews with two (2) teachers and thirty (30) students from the Once de Noviembre Educational Institution in Los Patios, Norte de Santander. Likewise, the project as a technique for collecting information, used non-participant observation and the development of environmental workshops. Likewise, the Institution's Educational Project, the teacher's parceler and the students' notebooks were analyzed. The research found that the impact generated is small. The communication model used is the traditional one based on orality and little participatory. The communication tools used by teachers are very few; the word, the blackboard and the marker are the most used, and these do not manage to generate an environmental culture in children in a participatory way.